An overview of current research on the modulation of NLRP3 inflammasome by traditional Chinese medicine to combat acute pancreatitis - He, Xiongjie; Xia, Jia; Chen, Qi; Huang, Zhaozhao; Lu, Juanjuan; Ren, Yisong (Frontiers in Molecular Biosciences, 2025)
Acute pancreatitis (AP), a life-threatening gastrointestinal emergency, is characterized by acute onset, rapid clinical deterioration, and high mortality rates, imposing profound long-term health burdens and socioeconomic costs on patients and healthcare systems. Current therapeutic strategies focus on supportive care, as no curative therapies exist to halt AP progression. Traditional Chinese medicine (TCM), with its multi-target, multi-component, and multi-pathway pharmacological properties, has emerged as a promising therapeutic drug against inflammation-driven pathologies, including AP. This review systematically discussed the assembly, activation, and pathogenic contributions of the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome in AP pathogenesis. Mechanistically, NLRP3 activation exacerbated pancreatic injury through caspase-1-dependent maturation of interleukin-1β (IL-1β) and gasdermin D (GSDMD)-mediated pyroptosis, perpetuating systemic inflammation. We systematically summarized the research progress of TCM in the treatment of AP by reducing pancreatic necrosis, neutrophil infiltration, and intestinal barrier dysfunction through targeting NLRP3 inflammasome, as well as its clinical evidence. Collectively, this review highlights the translational potential of TCM as an adjunctive therapy for AP through NLRP3 inflammasome inhibition, offering mechanistic insights and evidence-based support for its integration into integrative medicine strategies.